(3JaSjQ GHf HQLGfs - (3YHO GdSdGe Hf YHO GdQMef Hf eMeO GddNej GdETHjdj, CHh GdMce,J (B536 (3g` s
(3ChdgG (B:s
(3ef ShQI Bd YeQGf JaSjQ BjI Chd GdehLhO efg hdG JMSHf GdPjf bJdhG ai SHjd Gddg CehGJkG (B) (3Hbhdg HNdGa GdHOf hGdHOf JVYa HYO Gdhbha HNdGa GdQhM s
(3BNQgG (B:s
(3BNQ GdehLhO efg ChGNQ ShQI GdeGFOI (B: (3hGddg edc GdSehGJ hGdCQV heG ajgf hgh Ydi cd TF bOjQg Hbhdg (B: (3de jbd hef ajgf dGf eG CYe ef ef hCf eG ShGg djS HGdfSHI Edi Gddg Yde s
(3GdfSNI HgG MhGTs
(3LRA efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJaSjQ hYdhe GdbQBfs